Locked nucleic acid probes for enhanced detection of FLT3 D835/I836, JAK2 V617F and NPM1 mutations. Issue 10 (10th June 2011) - Warshawsky, Ilka; Mularo, Frank
Abstract : Aims: Detecting low-level clinically significant cancer-relevant somatic mutations can be difficult. Several technologies exist for detecting minority mutations. One method is locked nucleic acid (LNA) PCR. In this study, LNA probes were used to enhance the sensitivity for detecting FLT3 D835/I836 tyrosine kinase domain (TKD) mutations, the JAK2 V617F mutation and insertion mutations in the nucleophosmin 1 gene. Methods: PCR was performed with and without LNA probes using DNA known to contain FLT3 D835/I836 TKD, JAK2 V617F and NPM1 mutations. FLT3 D835/I836 TKD mutations were detected following EcoRV restriction enzyme digestion and capillary electrophoresis. The JAK2 V617F mutation was detected by melt-curve analysis. NPM1 insertions were detected by capillary electrophoresis. Results: The detection of FLT3 D835/I836, JAK2 V617F and NPM1 mutations was enhanced approximately 10–50-fold using LNA probes. Rare JAK2 double mutants gave abnormal blocking patterns with the LNA probe. Conclusions: Adding LNA probes to existing assays is a simple way to enhance and confirm the detection of mutations, especially those at low levels.